Work, labour and cleaning : the social contexts of outsourcing housework - Singha, Lotika (Gender and sociology., 2019)
Outsourcing of domestic work in the UK has been steadily rising since the 1970s, but little research has considered White British women. This book argues that outsourced domestic cleaning can either be done as mental and manual skilled work or as manual and 'natural' emotional/affective labour, depending on the work conditions.